Assessing house price dynamics in Lima - Diego Vilchez (Graduate Institute of International and Development Studies, 2015)
This paper uses a two-step procedure to analyze the long-run dynamics between real house prices and their fundamentals in Lima, Peru. In this framework, first a hedonic price index is calculated, and then used for estimating a quarterly vector error correction model over the period 1998-2014. The price determinants considered in this application are: real mortgage interest rate, real gross domestic product, and trading volume. The reduced form of the model is employed for generating alternative price forecasts. In addition, a structural decomposition of the system allows us to identify and give an economic interpretation to the permanent and transitory shocks. Finally, this analysis is also applied to different tranches of the price distribution to assess if the interrelationships in the system vary across them. Results imply that income and trading volume shocks contribute the most at explaining the dynamics in prices. Also, under reasonable assumptions for the modeled fundamentals, predictions suggest that real house prices would undergo an important deceleration during the following years. Some signs of differenced behavior throughout the price distribution in the housing market cannot be ruled out in this analysis.
Keywords: R21; E31; C32; 330; house prices; hedonic index; vector autoregression